Forked-roller feed MECHANISM for seed onion oriented planting - A. G. Aksenov; P. A. Emel’Yanov; V. A. Ovtov; A. V. Sibirev (Сельскохозяйственные машины и технологии)
Seed onion planting is fundamental operation at realization of technological process of onions cultivation. The main lack of bulb planters is a group picking of bulbs from overall mass by planting devices, but not single-piece wherefore planting of bulbs in demanded orientation is problematic. It was noted that when developing of bulb planters for planting of bulbous cultures it is necessary to provide optimum balance between productivity and quality indicators of planting: uniformity of distribution along a row and quantity of the bulbs with a stem below. It was established that the roller feeds are most perspective. There were defined their main shortcomings: seeds damage and lack of bulbs stem below orientation. Thus, uniformity of distribution makes about 40 percent. A special device with the orienting funnels was suggested. A forked-roller feed for the oriented seed onion planting for the oriented planting of seed onion carrying out single-piece picking of bulbs from the bunker and their giving in seed tube at below stem orientation for planting in a furrow was worked out. Researches confirmed that the suggested design provides stable performance of technological process of bulbs planting.